2022
DOI: 10.1101/2022.05.04.489851
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A DNase T6SS effector requires its MIX domain for secretion

Abstract: Bacteria use diverse classes of secreted polymorphic toxins to outcompete bacterial rivals. The MIX domain defines a widespread class of polymorphic type VI secretion system (T6SS) effectors, many of which are horizontally shared. Although several MIX-effectors have been investigated, the role of the MIX domain and the activity of many fused toxin domains remain unknown. Here, we use the Vibrio parahaemolyticus MIX-effector VPA1263 to demonstrate that MIX is necessary for T6SS-mediated secretion; however, we f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…MIX appears to be mainly located at the N-terminal region of the proteins, fused to C-terminal effector domains with antibacterial or anti-eukaryotic activity (Salomon et al, 2014). A recent work has shown that MIX sequence is necessary for the translocation of the effector from T6SS1 of Vibrio parahaemolyticus, demonstrating the importance of this signal in substrate recruitment (Fridman et al, 2022). Recently, it has been proposed that these sequences can be found not only in the effector protein, but also in a co-effector, which enables the loading and secretion of the toxin via the T6SS (Dar et al, 2022).…”
Section: Type VI Secretion Systemsmentioning
confidence: 99%
“…MIX appears to be mainly located at the N-terminal region of the proteins, fused to C-terminal effector domains with antibacterial or anti-eukaryotic activity (Salomon et al, 2014). A recent work has shown that MIX sequence is necessary for the translocation of the effector from T6SS1 of Vibrio parahaemolyticus, demonstrating the importance of this signal in substrate recruitment (Fridman et al, 2022). Recently, it has been proposed that these sequences can be found not only in the effector protein, but also in a co-effector, which enables the loading and secretion of the toxin via the T6SS (Dar et al, 2022).…”
Section: Type VI Secretion Systemsmentioning
confidence: 99%